Loading and Unloading Problems : Oil Prodcut with Stern Line Bunkering on MT. B Ace - Arisetya, Al - Ikhsani Ilham; Sapan, Yustina; Prayogo, Darul (Jurnal Navigsi Maritim, 2025)
Abstract: The Stern Bunkering process often encounters challenges, such as delays in fuel transfer, technical issues with equipment, or inconsistencies between operational procedures and field conditions. This study focuses on identifying the causes of delays and providing solutions to mitigate these challenges during bunkering operations on MT. B ACE. The research method of this thesis is qualitative descriptive. Data sources are taken from primary and secondary data. Data collection techniques using field research which includes interviews, observation and documentation so that data validity techniques are obtained. Data analysis techniques using Miles and Huberman which include data collection, data reduction, data presentation and conclusion drawing. The findings reveal two main factors causing delays in Oil Product loading and unloading through Stern Line Bunkering: internal and external factors. Internal factors include insufficient crew familiarization with safe loading and unloading methods, inadequate safety meetings, and technical issues such as entangled Towing Lines and Bunkering Hoses. External factors include unfavorable weather conditions, poor communication with receiving vessels, and limited bunkering facilities on purse seine fishing vessels. Keywords: Loading and Unloading, Operational Challanges, Stern Line Bunkering